The Meaning of Istighfar in The Qur’an (Charles Sanders Pierce Semiotic Analysis) - Andesra, Aan; Jannah, Miftahul (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research examines the meaning of Istighfar in the Qur'an, which has been understood as a form of asking for forgiveness, both in the form of actions and words Astagfirullah al-Adzim. However, in the Qur'an Istighfar can be interpreted broadly. The purpose of this study is to look at the signs of the word Istighfar in the Qur'an using a semiotic approach. In this case, the author uses Charles Sanders Pierce's semiotic theory, namely the trichotomy or triadic (Representamen, Object and Interpretant) to reveal the meaning of Istighfar as a sign. This research uses a qualitative approach with a library research method. The results showed that Istighfar is not only interpreted as a form of asking for forgiveness, either in the form of actions or words such as Astaghfirullah al-Adzim, but also means Fath al-Rizq (opening the door to sustenance), al-Ijabah (answered prayer), and Takziyat al-Qalb (cleansing the heart). This research contributes to the meaning of Istighfar and can provide insight for semiotic research.